Medical Education - Miller, M; Wee, B (Oxford University Press, 2011)
Medical education in the UK is undergoing radical change. Against a background of similar changes in the National Health Service (NHS) and in the public perception of professionals, this chapter tries to provide a snapshot of this rapidly changing landscape in medical education. In the UK, palliative medicine was established as a medical specialty within the Royal College of Physicians in 1987. Since 1993, under the reforms brought in by the then Chief Medical Officer, Sir Kenneth Calman, to comply with European regulations, those aiming to become specialist physicians in palliative medicine must undergo four years of higher specialist training. This chapter provides a basic understanding of how doctors are currently trained in the UK; the pathway from trainee to specialist physician in palliative medicine; and key issues and recent developments in medical education in the UK.